K KETERAMPILAN MEMBACA PEMAHAMAN MATERI RAGAM TEKS BERBASIS HOTS DI SD : STUDI LITERATUR: KETERAMPILAN MEMBACA PEMAHAMAN MATERI RAGAM TEKS BERBASIS HOTS DI SD : STUDI LITERATUR - Agnia, N Gina Siti; Yunus Abidin; Ai Sutini (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2024)
This research aims to examine the very low reading comprehension skills in Indonesia. It can be seen that the position of students' reading literacy skills in Indonesia from the results of several PIRLS surveys in 2006, IEA 2011, and PISA in 2018 can be categorized as very worrying. This international research assessment standard refers to advanced reading (comprehension) or what is often called HOTS (High Order Thinking Skills). The purpose of this article is to provide information regarding Indonesian students' ability to read comprehension with HOTS-based text variation material in Indonesian language learning, both regarding various problems that result in low reading comprehension skills and how to improve reading comprehension skills in elementary schools. This research uses qualitative research methods by studying literature or literature studies using several sources of written literature, data, and book references and other scientific journal articles. The results of the research show that reading comprehension problems are caused by incorrect comprehension orientation regarding advanced reading levels and lack of variety in learning to read questions in elementary schools so that reading comprehension skills are very low.